Faktor Faktor Resiko Kejadian Stroke Berbasis Stroke Risk ScoreCard - Marselia Dwiyanti Cahyaningtyas; Sri Puguh Kristiyawati; Novi Heri Yono (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Stroke is a fuctional disorder tahat manifest as nerve paralysis, resulting from either an obstruction of blood flow to the brain due to a lock of oxygen or a cessation of blood supply due to blockage or bleeding. The risk factors are blood pressure, cholesterol, history of diabetes mellitus, history of smooking, atrial fibrillation, body mass index, physical activity, and family history of stroke. This study aims to determine the factors associated with stroke incidence. This typeof researchis descriptive and has a retrospective study design. The sampling technique used was accidental sampling wit a sample size of 60 respondents, where the population was 4355stroke patients. The research results used the stroke risk scorecard (SRSC)measuring tool. The statistical is Chi-square. The research results showed that the majority of respondents were erderly, aged 46-65 tahun years (80,0%), male (50,0%), female (50,0%) and had comorbid hypertension (56,7%). N The Chi-square test revealed several risk factors, including blood pressuare, a history ofdiabetes mellitus,smoking history, atrial fibrilation, BMI, and family history of risk. Menwhile, the results of the multiple linear regression test show that the most dominant variable is physical activity, with a standardized cooefficient betta valueof 0,366. It is hoped that the results of this research can be used as a basis for input for health servise providers to provide comprehensive nursing care for stroke patients.